Extraction of transcribing SV40 chromosomes in very low salt. - Edenberg, H J (1980)
SV40 chromosomes capable of continued RNA synthesis in vitro have been extracted from infected cells in solutions of very low ionic strength (5 mM HEPES, 0.25 mM MgCl2). The RNA made is of high molecular weight, and synthesis is sensitive to alpha-amanitin. More RNA is made than from previously described (high salt-extracted) transcription complexes. Transcribing SV40 chromosomes sediment at a rate intermediate between replicating and mature chromosomes, and have a higher ratio of protein to nucleic acid than either. They retain proteins that are lost during exposure to high salt, and might prove valuable in identifying proteins involved in SV40 transcription.